Practices of Agribusiness in Soccsksargen (Region Xii) and their Perceived Financial Performance: A Mixed Method - Pomar, Melvin; Ali, Emraida; Ali, Noraida (International Journal of Management Excellence (ISSN: 2292-1648), 2021)
ABSTRACT This study was conducted primarily to analyze practices of agribusiness in SOCCSKSARGEN (Region XII). A qualitative-quantitative research design was used in this study. This study used exploratory sequential mixed method. In the exploratory sequential approach, the researcher first begins with a qualitative research phase and explores the views of participants. The data were analyzed and the results were then used to develop the survey questionnaire. The business practices of Agribusiness in SOCCSKGEN (Region XII) as to technology and innovation, knowledge in business, research and development, marketing mix, employee relation, and management functions/skills is evident. The marketing mix reflects with highest standardized beta coefficient which entails that among the practices of agribusiness in SOCCSKSARGEN (Region XII), the marketing mix is the significant indicator to the perceived financial performance of the agribusiness enterprises in the region. Only the length of service offers significant contingent effect. The four (4) moderating variables (Length of Business Operation, Type of Business Activities, Type of Management, and Position) offer no contingent effect to the relationship of the independent and dependent variables. Keywords: Agribusiness, Marketing Mix, Employee Relations, Exploratory Sequential Mixed Method, Perceived Financial Performance, Length of Service